The geography of the soils of Bangladesh - Brammer, H. (Dhaka, Bangladesh : University Press, 1996)
Revised and up-dated edition of a report prepared for the Food and Agriculture Organization of United Nations.
Includes bibliographical references and index.
Keywords: Soils -- Bangladesh